2021
DOI: 10.3390/cancers13071499
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Equivalents of TET2 Mutations

Abstract: TET2 is a dioxygenase dependent on Fe2+ and α-ketoglutarate which oxidizes 5-methylcytosine (5meC) to 5-hydroxymethylcytosine (5hmeC). TET proteins successively oxidize 5mC to yield 5-hydroxymethylcytosine (5hmC), 5-formylcytosine (5fC), and 5-carboxylcytosine (5caC). Among these oxidized methylcytosines, 5fC and 5caC are directly excised by thymine DNA glycosylase (TDG) and ultimately replaced with unmethylated cytosine. Mutations in TET2 have been shown to lead to a hypermethylated state of the genome and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 77 publications
0
9
0
1
Order By: Relevance
“…hsa-mir-3123 is downregulated in insulin receptor haploinsufficient hepatic stellate cells [ 83 ]. hsa-miR-4775 is associated with diabetic nephropathy and its role in targeting apoptotic pathway’s core genes [ 84 , 85 ]. hsa-miR-1236-3p is reported to be involved in apoptosis induction [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…hsa-mir-3123 is downregulated in insulin receptor haploinsufficient hepatic stellate cells [ 83 ]. hsa-miR-4775 is associated with diabetic nephropathy and its role in targeting apoptotic pathway’s core genes [ 84 , 85 ]. hsa-miR-1236-3p is reported to be involved in apoptosis induction [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leukemic IDH1 and IDH2 mutations disrupt TET2 function and impair hematopoietic differentiation [ 30 , 31 ]. As TET2 function is dependent on the metabolites produced by the IDH proteins [ 21 , 32 ], susceptibility to STAT5 and MCL1 inhibitors may be similar in AML cells with IDH mutations, as in TET2 mutated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Hematopoietic cytokine receptor signaling is largely mediated by JAKs and their downstream transcription factors, the STATs [ 7 ]. Mutations in the tumor suppressors IDH1/2 and TET2 may be functionally equivalent [ 21 ]. The tumor suppressor FoxP3 may inhibit AKT and its downstream target MCL-1 [ 22 , 23 ].…”
Section: Figurementioning
confidence: 99%
“…As an important tumor suppressor gene related to epigenetic modification, the mechanism of TET2 gene regulation remains unclear ( 36 ). At the pre-mRNA level, multiple studies have confirmed that microRNAs [miR-22, miR-29, miR-101 and miR-125] negatively regulate TET2 expression ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study suggested that cell metabolism was accelerated under hypoxic conditions and that hypoxia may serve certain roles, such as promoting proliferation and inducing apoptosis in the pathogenesis of AML. As an important tumor suppressor gene related to epigenetic modification, the mechanism of TET2 gene regulation remains unclear (36). At the pre-mRNA level, multiple studies have confirmed that microRNAs [miR-22, miR-29, miR-101 and miR-125] negatively regulate TET2 expression (37,38).…”
Section: Discussionmentioning
confidence: 99%